DISCOVERING THE STRATEGY FOR WHOLE SYSTEM MODELING. Issue 2 (July 2017) - Ring, Jack
ABSTRACT: This paper presents an interim report of an inquiry into the strategy for evolving to a whole system modeling capability. The ability to accurately anticipate the behaviour of a whole system is key to system engineering of all kinds. Currently, it is the larger unknown. A strategy specifies the allocation and scheduling of capabilities that will moderate impediments sufficiently to enable achievement of objectives. Pending refinement, the objective for the year 2015 envisions approximately 100, 000 practitioners performing whole system modelling, worldwide, at ten‐fold better productivity and innovation than exists today. The inquiry to date has identified impediments, selected key impediments, and discovered their relative influence pattern. Also identified is a key subset of foreseeable capabilities that could moderate the impediments. The gap between these two profiles indicates our profession's readiness to meet the challenge. This paper presents the results to date and describes work remaining.